Kontribusi Latar Belakang Pendidikan Mahasiswa PAI terhadap Penguasaan Mata Kuliah Studi Hadis di UIN SUSKA Riau - Febri Widiandari (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The purpose of this study was to find out how much the educational background contributed to the mastery of hadith study courses by PAI students at UIN SUSKA Riau. The research approach that the authors use is quantitative research. Data collection techniques that the authors use are tests, questionnaires and documentation. While the data analysis technique that the authors use is simple linear regression. The results of this study indicate that the magnitude of the contribution of educational background to the mastery of Islamic education students' hadith studies courses is 1.7% and the remaining 98.3% is influenced by other factors. These other factors can be internal factors such as intelligence, students towards the material they are studying, the tendency of students to pay attention and remember various activities, talents, and willingness to respond. While external factors such as family, school and community factors.